PERBEDAAN BENTUK KRENDET DAN LAMA PERENDAMAN TERHADAP HASIL TANGKAPAN LOBSTER (PANULIRUS SP.) DI PERAIRAN CILACAP - Mubin, Akhmad Fadhlul; Boesono, Herry; Sardiyatmo, Dr. (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Lobster (Panulirus sp.) is one of the export commodities from fisheries which gives a quite high contribution of fisheries world, and has an important economic value. This high economic value are encouraging fisherman to catch lobster continuously. One of the fishing gear that can be operated is krendet. Krendet is a fishing gear that operated passively by the use of bait as atracted lobster. The purpose of this research are to understand and analyze the effect of different form of krendet, length of immersion differences and also the interaction between forms and length immersion towards the catches of lobster in cilacap water boundaries. The materials used were boat as transportation, krendet, and GPS to determain position. The method used in the research is experimental fishing method with 16 repetitions and 4 times treatments. The analyze of the data was used in this research normality test and ANOVA test with SPSS 17.0. The result showed the used of krendet forms and the length of immersion differences affected to the catches where the square shape and 12 hours of immersion are giving more catches. There is no interaction effect between krendet forms and length of immersion towards the catches of lobster.